Production of biomass of photosynthetic bacteria on base of stock-breeding and poultry wastes - A. Kh. Paronyan; A. V. Gasparyan (ՀՀ ԳԱԱ հրատ.)
On base of stock-breeding and poultry wastes the cheap nutrient media for cultivation and production of biomass of phototrophic bacteria have been developed. Cultivation of purple nonsulfur bacteria Rhodobacter sphaeroides together with Bacillus megaterium in mixed culture has been succeeded in high biomass yield. The obtained biomass was distinguished with rich contents of biologically active substances. Անասնապահական և թռչնաբուծական թափոնների հիման վրա մշակվել են էժան սննդամիջավայրեր ֆոտոտրոֆ բակտերիաների աճեցման և կենսազանգվածի ստացման համար։ Կիրառելով խառը կուլտուրաների՝ Rhodobacter sphaeroides ոչ ծծմբային ծիրանագույն բակտերիաների և Bacillus megaterium□ի համատեղ աճեցումը, հաջողվել է զգալի բարձրացնել կենսազանգվածի ելքը։ Ստացված կենսազանգվածը առանձնանում է կենսաբանական ակտիվ միացությունների հարուստ պարունակությամբ։ Разработаны дешевые питательные среды на основе животноводческих и птицеводческих отходов для выращивания и получения биомассы фототрофных бактерий. С использованием смешанного культивирования несерных пурпурных бактерий Rhodobacter sphaeroides и Bacillus megaterium удалось заметно увеличить выход биомассы. Полученная биомасса отличается богатым содержанием биологически активных соединений.
Keywords: Biology; Microbiology